Agricultural Ethics in East Asian Perspective A Transpacific Dialogue (The International Library of Environmental, Agricultural and Food Ethics,, 2018)
This book brings together agricultural ethics scholars from the US, Japan and Taiwan to discuss crucial issues in agricultural ethics and sustainability ethics in comparative context. Agricultural ethics and sustainability ethics are wide-ranging and closely linked to environmental ethics, bioethics, virtue ethics, animal welfare, soil conservation, not to mention rural traditions and lifestyles. Six of the chapters cover historical traditions and values in Europe, the US and East Asia. Four of the chapters cover the role of virtue ethics in the analysis of agrarian and environmental ethics, agricultural biotechnology, food ethics, and alternative agriculture, respectively. Finally, two of the chapters cover field efforts of agricultural ethics involving preserving agricultural heritage and building consensus for sustainable farming, respectively. Although the papers are divided into three groups, their contents are interconnected and mutually informative.